2020
DOI: 10.21203/rs.2.24736/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative cardiovascular safety of GLP-1 receptor agonists versus other glucose-lowering agents in real-world patients with type 2 diabetes: a nationwide population-based cohort study

Abstract: Background : Current evidence about the cardiovascular safety of glucagon-like peptide-1 receptor agonist (GLP-1ra) possesses limited generalizability to real-world patients with type 2 diabetes (T2D) in usual practice. This study aimed to investigate the comparative cardiovascular safety of GLP-1ra in head-to-head comparisons with dipeptidyl peptidase-4 inhibitor (DPP-4i), sulfonylurea (SU), and insulin in a real-world population with T2D. Methods : Adults with newly-diagnosed T2D were identified from Taiwan’… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…GLP-1 RAs are known to reduce blood pressure (BP) [14] and body weight [15]. Large cohort studies and meta-analyses of RCTs demonstrated that GLP-1 RAs improve cardiovascular outcomes [16][17][18][19][20] The American Diabetes Association (ADA) recommends SGLT-2 inhibitors or GLP-1 RAs in type 2 DM patients who have atherosclerotic cardiovascular disease or kidney disease [21]. However, it remains unclear if GLP-1 RAs are beneficial to type 2 DM patients with CKD as well.…”
Section: Introductionmentioning
confidence: 99%
“…GLP-1 RAs are known to reduce blood pressure (BP) [14] and body weight [15]. Large cohort studies and meta-analyses of RCTs demonstrated that GLP-1 RAs improve cardiovascular outcomes [16][17][18][19][20] The American Diabetes Association (ADA) recommends SGLT-2 inhibitors or GLP-1 RAs in type 2 DM patients who have atherosclerotic cardiovascular disease or kidney disease [21]. However, it remains unclear if GLP-1 RAs are beneficial to type 2 DM patients with CKD as well.…”
Section: Introductionmentioning
confidence: 99%
“…Fifth, due to limited numbers of study subjects in different individual GLP-1RA and insulin therapies, further assessment of comparative effectiveness and cost-effectiveness of treatments by the more granular level of different individual drugs would be underpowered. Moreover, given no heterogeneous treatment effects found by age, gender, or diabetes severity for GLP-1RAs versus insulin in our previous analyses [6] and limited study subjects with different patient characteristics in the present study, performing the costeffectiveness analysis stratified by different patient demographic or clinical characteristics would be infeasible. Therefore, future research with sufficient study subjects that can be classified by different individual drugs and patient characteristics is encouraged, which can provide more individualized and precise suggestions on treatment selections.…”
Section: Study Limitationsmentioning
confidence: 97%
“…S2. The comparability of patient characteristics between two study groups was achieved by the three-step matching on (1) the index date, (2) prior exposure to GLAs in the year before the index date, and (3) patient demographic and clinical characteristics (e.g., diabetes severity, comorbidities, co-medications for cardiovascular diseases [CVDs]) using the propensity score matching approach [6]. After the matching, there were 1022 matched pairs of GLP-1RA and insulin users with no significant between-group difference in the baseline characteristics except for age, hyperlipidemia, and neuropathy (Additional file 1: Table S3).…”
Section: Data Source and Cohort Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a two-step matching algorithm was implemented to enhance the comparability between study groups of DPP4i and SU users. 25 First, the previous utilization patterns of GLAs were considered as an important proxy for patients' underlying status of diabetes management and therefore utilized as the matching criterion. Specifically, patients exposed to the same number of GLA classes were matched first, with a maximum 90-day drug supply difference (±45 days) of prior use of DPP4is or SUs allowed for the matched pairs.…”
Section: Cohort Identificationmentioning
confidence: 99%